Expressão diferencial de genes em sementes osmocondicionadas e plântulas de Physalis angulata L. e prospecção de constituintes seco-esteroidais em plantas submetidas a estresse abiótico - Souza, Manuela Oliveira de (2012)
Abiotic stresses as salt stress and water restriction are considered responsible for causing changes in physiological processes, with detrimental effects on the germination seeds, growth and development of plants. Priming seeds and seedlings can improve their performance, rate of germination and seedling emergence under normal and abiotic stress conditions. Although recognized as a particularly harmful, induction of stress has been used in recent decades due to modulate the production of secondary metabolites in plants. The evaluation of gene expression allows one to understand how the adjustment occurs in the synthesis of proteins able to protect the plant tissues from the effects caused by different stresses. The aim of this study was looking for how priming enhance seed germination rates under abiotic stress and to get more vigorous seedlings, from the expression profile of genes related to salinity and production of seco-steroidal plant Physalis angulata subjected to water restriction and salt stress. Primed and non primed seeds were subjected to different salt solutions. We evaluated parameters of germination, and gene expression in seeds and seedlings. The growth and the content of seco-steroid were evaluated in plants of P. angulata grown under experiments in greenhouse. Priming positively affected germination rates of seeds and seedlings to have provided the expression of some genes APX, GST and thioredoxin, which are related to protection against oxidative stress. The treatments performed induced an increase in the seco-steroidal content in leaves and decrease in stems of P. angulata.